Odpowiedzi

2010-03-17T19:35:35+01:00
-1/3x +1/4=1/4x-2/3
-7/12x=-11/12/:(-7/12)
x=11/7
x=1 i 4/7

x+2/3 +1=-(2x+1/15)
x+2/3+1=-2x-1/15
x+2x=-1/15-2/3-1
3x=-1/15-10/15-1
3x=-11/15-1
3x=-1 i 11/15/:3
x=13/15

licze na maxa;)
Najlepsza Odpowiedź!
2010-03-17T19:37:14+01:00
-1/3x +1/4=1/4x-2/3 /*12
12*(-1/3x + 1/4) = 12* (1/4x - 2/3)
-12/3x + 12/4 = 12/4x - 24/3
-4x + 3 = 3x - 8 /+8
-4x + 11 = 3x /+4x
11 = 7x /:7
1 57/100 = x
...

x+2/3 +1 = -(2x+1/15)
x+2/3+1 = -2x -1/15 /*15
x+30/3+1 = -2x - 15/15
x+10 + 1 = -2x - 1
x+11 = -2x - 1 /+2x
3x+11 = 1 /-11
3x = -10 /:3
x = 3 1/3

myślę że pomogłam [właśnie teraz to biorę więc jest dobrze]